alt="Image"/> z.
(6). If y
(7). If it is false that x
By Rules I and III,
(8). It is either false that v
By Rule II,
(9). Either v
[Note B. An entire calculus of logic might be made with the sign
x
If x
(v
But such a calculus would be useless on account of its complexity.]
[Note C. The equation x = y means, of course, that x and y are at the same point of the scale. That is to say, the definition of x = y is contained in the following propositions:
A. If x = y, x
B. If x = y, y
C. If x
From these propositions, it follows that logical equality is subject to the following rules:—
i. x = x.
ii. If x = y, then y = x.
iii. If x = y and y = z, then x = z.
iv. Either x = y or y = z or z = x.
The proof of these from A, B, C, by means of Rules I, II, III, is left to the student.]
§3. LOGICAL ADDITION AND MULTIPLICATION
[Note. The sign
Any two numbers whatever (say 5 and 2) might be chosen for u and v, the representatives of the false and the true; though there is some convenience in making v the larger. Then, the principle of contradiction is satisfied by these being different numbers; for a number, x, cannot at once be equal to 5 and to 2, and therefore the proposition represented by x cannot be at once true and false. But in order to satisfy the principle of excluded middle, that every proposition is either true or false, every letter, x, signifying a proposition must, considered as a number, be supposed subject to a quadratic equation whose roots are u and v. In short, we must have
(x − u)(v − x) = 0.
Since the product forming the left hand member of this equation vanishes, one of the factors must vanish. So that either x − u = 0 and x = u, or v − x = 0 and x = v. Another way of expressing the principle of excluded middle would be:
It will be found, however, that occasion seldom arises for taking explicit account of the principle of excluded middle.
The propositions
Either x is false or y is true,
and
Either y is false or z is true,
are expressed by the equations
(x − u)(v − y) = 0
(y − u)(v − z) = 0.
For, as before, to say that the product forming the first member of each equation vanishes, is equivalent to saying that one or other factor vanishes.
Let us now eliminate y from the above two equations. For this purpose, we multiply the first by (v − z) and the second by (x − u).
We, thus, get
(x − u)(v − y)(v − z) = 0
(x − u)(y − u)(v − z) = 0.
We now add these two equations and get
(x − u)(v − u)(v − z) = 0.
But the factor v − u does not vanish. We, therefore, divide by it, and so find
(x − u)(v − z) = 0.
The signification of this is,
Either x is false or z is true;